Literacy of Contracts for the Procurement of Goods and/or Services to Village Government Officials - Kuahaty, Sarah Selfina; Pesulima, Theresia Louize; Sinaga, Roulinta Yesvery (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: The suboptimal use of village funds is due to the lack of understanding and knowledge among village government officials and Human Resources (HR) regarding proper procurement procedures, including drafting effective procurement contracts. This suggests that procurement of goods and services could potentially lead to legal issues.Purposes of The Devotion: The purpose of this community service is to transform information and legal knowledge related to the technique of Procurement of goods and/or services contract drafting from Village funds and village fund allocations.Method of The Devotion: The outreach activities are carried out by conveying counseling, discussions and training.Results Main Findings of the Devotion: Improving the understanding of staff government Sanahu village regarding contract procurement for goods and/or services is carried out to provide education on agreement law in the implementation of procurement whose funding sources come from Village Funds and Village Fund Allocations. The legal education provided is to provide an understanding of the basic concepts of agreement law, dissemination of the procedures procurement for goods and/or services in the village; and training in procurement contract drafting using simple position cases related to the procurement of office stationery for staff government Sanahu village.